Faktor-faktor yang mempengaruhi voluntary disclosure pada perusahaan yang terdaftar di Bursa Efek Indonesia - Hendi Hendi; Kelvin Dharmawan (MBR (Management and Business Review), 2021)
The purpose of this research is to examine the factors influencing the voluntary disclosure of a company and the level of disclosure made by the company. Secondary data in this study were obtained from the company's annual report on the Indonesia Stock Exchange (IDX). Purposive sampling is being used sampling method. The number of samples was 2.230 company annual reports. Data is being processed using Panel Regression Analysis through Eviews 10 and SPSS 22. This research led to the conclusion that the variables company size, leverage, managerial ownership, and board independence have the results of a positive significant effect on voluntary disclosure. Significantly negative results have an effect on voluntary disclosure owned by foreign ownership variables, while other variables namely profitability, state ownership, institutional ownership, the board size, and type of external auditor have no significant effect on voluntary disclosure variables.